Wrinkle prediction of seat cover considering cyclic loading-unloading with viscoelastic characteristics. (5th November 2016) - Oh, Jeong Seok; Kim, Dae Young; Kim, Heon Young; Lee, Chung An; Bang, Jun Ho; Choi, Kwon Yong
Abstract: The purpose of this study is to predict the wrinkling of leather seat covers created by repeated loading–unloading conditions and long-term driving conditions. To predict wrinkling, this paper describes a numerical analysis process and material test methods. Viscoelasticity is considered to express the time-dependent deformation of the seat cover and a leather material is selected. To evaluate the viscoelastic behavior of leather seat covers in accordance with time and the number of times being seated, cyclic tests are conducted using leather specimens of a strip type. In the cyclic tests, one cycle consisted of loading–creep–unloading conditions; the viscoelastic (creep) time is 1 h, and the total repeated number is 60. To perform the seating simulation, PAM-COMFORT, a commercial software package for seat modeling, is used, and permanent deformation of the seat cover is predicted. It can be difficult to predict viscoelasticity using explicit code. As such, a material modeling and evaluation process is suggested. Test results obtained using a model construct are compared with experimental test results with good agreement. The numerical process is then applied to a seat module with an HPM1 dummy model, and quantitative wrinkle deformation is predicted. The proposed process was used to determine the material properties that had deteriorated due to the viscoelastic characteristics of the seat covers. The viscoelastic effects on wrinkle occurrence were confirmed analytically by applying these properties to the seat modules. Graphical abstract: Highlights: This study predicts the wrinkling of seat covers created by repeated loading–unloading and long-term driving conditions. To predict wrinkling, this paper describes a numerical analysis process and material test methods. To perform the seating simulation, PAM-COMFORT, a commercial software package for seat modeling, is used The numerical process is applied to a seat module with an HPM1 dummy, and quantitative wrinkle deformation is predicted.